THE WORSHIP OF THE FORCES OF NATURE UNDER ISLAM AND ITS IMPACT ON AFRICAN SOCIETY FROM THE FIFTH CENTURY AH UNTIL THE END OF THE TENTH CENTURY AH - Farah Mustafa Qassem Al-Moussawi; Karim AtiAl-Khuzaie (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Nature worship is a religious and spiritual practice that focuses on the worship of spirits that exist in nature, and this worship is the main source of knowledge of the mythology of African peoples. They are firmly established despite their entry to Islam, and here it does not mean the weakness of religion in the African, but Islam has spread gradually, as there were neighboring tribes, Muslims with pagans, in addition to the rapprochement between the Islamic religion and African beliefs.